Caring fathers in Europe: Toward universal caregiver families? - Martínez-Pastor, Juan I.; Jurado-Guerrero, Teresa; Fernández-Lozano, Irina; Castellanos-Serrano, Cristina (Gender, Work & Organization, 2023)
Increasingly, men are challenging the assumption that care is a feminine task and are involving themselves in childcare and the care of dependent adults. However, this does not necessarily have consequences for their work, as they very rarely make costly adaptations in their working lives. In this study, we propose a definition of a man in care (MIC) as a working father who, in order to meet care needs, has adapted his working life in a way that potentially entails a financial penalty. We analyze the prevalence of men in care among men living with children below the age of 15 across the EU-27 plus Iceland, Norway, Switzerland, and the UK using recent representative data (the European Labour Survey and its 2018 ad hoc module on work-life balance). We find that although the number of men engaging in costly work adaptations is still very low when compared to their female counterparts, the characteristics of these men can be clearly outlined: they have a non-manual occupation (managers excluded), they have temporary contracts or are self-employed, they are partnered to women who hold jobs of 40 or more hours a week and have a high educational attainment, and they work in family-friendly companies. Also, at the context level, the prevalence of MIC is clearly related to gender equality and values. However, we do not find evidence of any country having reached the universal caregiver model proposed by Nancy Fraser, including those with more advanced gender and welfare regimes.